A new face of Borjeson–Forssman–Lehmann syndrome? De novo mutations in PHF6 in seven females with a distinct phenotype. Issue 12 (3rd October 2013) - Zweier, Christiane; Kraus, Cornelia; Brueton, Louise; Cole, Trevor; Degenhardt, Franziska; Engels, Hartmut; Gillessen-Kaesbach, Gabriele; Graul-Neumann, Luitgard; Horn, Denise; Hoyer, Juliane; Just, Walter; Rauch, Anita; et al.
Abstract : Background: Borjeson–Forssman–Lehmann syndrome (BFLS) is an X-linked recessive intellectual disability (ID) disorder caused by mutations in the PHF6 gene and characterised by variable cognitive impairment, a distinct facial gestalt, obesity, and hypogonadism. Female carriers are usually not affected or only mildly affected, and so far only two females with de novo mutations or deletions in PHF6 have been reported. Methods and results: We performed PHF6 mutational analysis and screening for intragenic deletions and duplications by quantitative real-time PCR and multiplex ligation dependent probe amplification (MLPA) in female patients with variable ID and a distinct appearance of sparse hair, remarkable facial features, hypoplastic nails, and teeth anomalies. We detected two truncating mutations and two duplications of exons 4 and 5. Furthermore, two female patients with PHF6 deletions and a similar phenotype were identified by routine molecular karyotyping. Recently, two patients with a clinical diagnosis of Coffin-Siris syndrome in early infancy had been found to harbour mutations in PHF6, and their phenotype in advanced ages is now described. Further studies revealed skewed X-inactivation in blood lymphocytes, while it was normal in fibroblasts, thus indicating functional mosaicism. Conclusions: Our findings indicate that de novo defects in PHF6 in females result in a recognisable phenotype which might have been under-recognised so far and which comprises variable ID, a characteristic facial gestalt, hypoplastic nails, brachydactyly, clinodactyly mainly of fingers IV and V, dental anomalies, and linear skin hyperpigmentation. It shows overlap with BFLS but also additional distinct features, thus adding a new facet to this disorder.